KONFLIK BATIN TOKOH KAWI MATIN DALAM NOVEL KAWI MATIN DI NEGERI ANJING KARYA ARAFAT NUR: KAJIAN PSIKOANALISIS SIGMUND FREUD (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the forms of inner conflict experienced by the main character, Kawi Matin, in the novel Kawi Matin di Negeri Anjing by Arafat Nur based on Sigmund Freud’s psychoanalytic theory, as well as to analyze the factors that cause these inner conflicts. This research employs a qualitative method with a descriptive approach. The primary data source is the novel published in 2020, consisting of 172 pages. Data were collected through reading and note-taking techniques, while data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The validity of the data was tested through source, technique, and time triangulation to ensure the reliability of the findings.The results of the study indicate that the inner conflict experienced by Kawi Matin is dominated by the ego aspect with 55 quotations, followed by the superego with 25 quotations, and the id with 23 quotations. The dominance of the ego reflects the character’s effort to maintain psychological balance rationally in dealing with traumatic situations and environmental pressures. Meanwhile, the id and superego aspects reveal a conflict between instinctual drives and moral values that triggers inner anxiety.The most dominant factor causing inner conflict is the need for safety, with 42 quotations. This is followed by the need for love and belonging with 27 quotations, esteem needs with 24 quotations, physiological needs with 7 quotations, and self-actualization needs with 3 quotations. These findings indicate that the character’s inner conflict is influenced by the interaction of personality structures and the unfulfilled basic needs within a repressive social condition.